Aaron Burr papers - Burr, Aaron, 1756-1836.
Correspondence, legal papers, accounts, and other papers relating primarily to the Burr conspiracy and trial. Includes a subpoena requiring Thomas Jefferson and others to testify at Burr's trial. Correspondents include Platt H. Crosby, Isaac Guion, John Greenwood, Edward Greswold, Gurdon William Lathrop, Isaac Mason, James Monroe, John Robert, Marinus Willett, and Christopher Peter Yates.
In part, positive photocopies and typewritten transcripts.
U.S. vice-president, U.S. senator from New York, and lawyer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Crosby, Platt H. -- Correspondence; Greenwood, John, -- 1760-1819 -- Correspondence; Greswold, Edward -- Correspondence; Guion, Isaac, -- -1823 -- Correspondence; Lathrop, Gurdon William, -- 1790-1832 -- Correspondence; Jefferson, Thomas, -- 1743-1826.; Mason, Isaac -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Robert, John, -- active 1802 -- Correspondence; Willett, Marinus, -- 1740-1830 -- Correspondence; Yates, Christopher Peter, -- 1750-1815 -- Correspondence; Burr Conspiracy, 1805-1807.; Trials (Treason) -- United States; Lawyers; Senators, U.S. Congress -- New York (State); Vice-Presidents -- United States